P522 Effectiveness of tofacitinib in a real-world Israeli cohort of patients with moderate-severe ulcerative colitis. (27th May 2021) - Avni Biron, I; Bar-Gil Shitrit, A; Koslowsky, B; Kopylov, U; Levartovsky, A; Weisshof, R; Aviv-Cohen, N; Maharshak, N; Hovel, D; Naftali, T; Goren, I; Snir, I; et al.
Abstract: Background: We sought to define the effectiveness of tofacitinib in a real-world (RW) cohort of patients with moderate to severe ulcerative colitis (UC). Methods: This was a multi-center retrospective observational cohort study (2017–2020). Clinical response and remission were defined as a reduction in Simple Clinical Colitis Activity Index (SCCAI) or partial Mayo score (PMS) of ≥3, and SCCAI ≤2 or a PMS ≤1, respectively. Results: We included 73 patients (47% male; median age 26 years [IQR 19.5–39.5], disease duration 7 years [IQR 2.5–14.5], follow-up 7.1 months [IQR 3–12]), 91% biologics-experienced, and 74% ≥ 2-biologics. Half of patients used concomitant steroids. Overall, 56.1% discontinued therapy due to either lack of response and/or adverse events (AEs), median time to discontinuation - 9.7 months (IQR 3.4–16). Based on per-protocol analysis, after induction (week-8–16), 33.3% achieved response, 23.3% remission, and 19% corticosteroid free remission. At early maintenance (week 26), 50% achieved response, 26.8% remission, and 24.4% corticosteroid free remission. There were no differences between biologics-experienced and naïve patients. Seventeen patients (23.2%) had an AE: herpes zoster- 2.7%, hospitalization- 12.3%, and colectomy- 2.7%. Remitters had higher albumin level compared with non-remitters (4.2±0.35 Vs. 3.8±0.35, P =0.023, respectively). Conclusion: In this multicenter RW cohort of highly biologics - experienced patients with UC, those who continued tofacitinib throughout induction achieved 50% response and 27% remission. Tofacitinib was well-tolerated.